Metabolic dysfunction-associated fatty liver disease increased the risk of subclinical carotid atherosclerosis in China - Lei, Fang; Wang, Xiao-Ming; Wang, Changquan; Huang, Xuewei; Liu, Ye-Mao; Qin, Juan-Juan; Zhang, Peng; Ji, Yan-Xiao; She, Zhi-Gang; Cai, Jingjing; Li, Huo-ping; Zhang, Xiao-Jing; et al. (Frontiers in Endocrinology, 2023)
Background & Aims: Metabolic dysfunction-associated fatty liver disease (MAFLD) was proposed to substitute NAFLD in 2020. This new term highlights the systematic metabolic disturbances that accompany fatty liver. We evaluated the correlations between MAFLD and subclinical carotid atherosclerosis (SCA) based on a nationwide health examination population in China. Methods: We performed a nationwide cross-sectional population and a Beijing retrospective cohort from 2009 to 2017. SCA was defined as elevated carotid intima-media thickness. The multivariable logistic and Cox models were used to analyze the association between MAFLD and SCA. Results: 153,482 participants were included in the cross-sectional study. MAFLD was significantly associated with SCA in fully adjusted models, with an odds ratio of 1.66; 95% confidence interval (CI): 1.62-1.70. This association was consistent in the cohort, with a hazard ratio (HR) of 1.31. The association between baseline MAFLD and incident SCA increased with hepatic steatosis severity. Subgroup analysis showed an interaction between age and MAFLD, with a higher risk in younger groups (HR:1.67, 95% CI: 1.17-2.40). Conclusion: In this large cross-section and cohort study, MAFLD was significantly associated with the presence and development of SCA. Further, the risk was higher among MAFLD individuals with high hepatic steatosis index and young adults.